ANALISIS PRESTASI KERJA PERSEMAIAN PADA AREAL KEBUN BIBIT PUTERA PANNJALU UPT CEMPAKA DI KECAMATAN CEMPAKA BANJARBARU KALIMANTAN SELATAN - Nur Vitta Sari; Arfa Agustina Rezekiah; Daniel Itta (Jurnal Sylva Scienteae, 2021)
The achievement of this work is done to identify the necessary work time in the nursery of the Putera Pannjalu seed Garden by knowing the level of efficient work achievement. This research aims to calculate the performance of work on seedlings at the Putera Pannjalu Nursery TIU (Technical Implementing Unit) Cempaka. The working time measurement uses a Cumulative method. Cumulative method is a method used in the actual work time measurement of any working element that the hand continues to run without returning to zero to the end. Work time measurement is performed on each activity cycle. Measuring the performance of seedlings in the plantation of PT. Putera Pannjalu TIU Cempaka consists of filling activities such as polybag, weaning, watering, maintenance and grow grass. Working performance measurement time at 07:30 am to 16:30 pm for seven days. The result of the polybag filling measurement is done by three workers with an average obtained for one week produce 202 polybag/hour/person, for the weaning activities by three workers with an average of 639 polybag/hour/person. While in measuring the performance of watering work performed by two workers get an average work performance of 79,838 polybag/hour/person. On the treatment activities acquired average of 19,739 polybag/hour/person and for the average performance of the work of the material of 14,898 polybag/hr/person. The results of the measurement of work performance in the Putera Pannjalu nursery of TIU Cempaka are influenced by age, sex and duration of work.Prestasi kerja ini dilakukan untuk menidentifikasi waktu kerja yang diperlukan di persemaian Kebun Bibit Putera Pannjalu dengan mengetahui tingkat prestasi kerja yang efisien. Penelitian ini bertujuan untuk menghitung prestasi kerja pada kegiatan persemaian di Kebun Bibit Putera Pannjalu UPT (Unit Pelaksana Teknis) Cempaka. Pengukuran waktu kerja menggunakan metode berturut (Cumulative). Metode berturut (Cumulative) merupakan metode yang digunakan dalam pengukuran waktu kerja yang sesungguhnya dari setiap elemen kerja yang jarum jam nya terus berjalan tanpa kembali ke nol sampai akhir. Pengukuran waktu kerja dilakukan pada setiap siklus kegiatan. Pengukuran prestasi kerja persemaian di kebun Bibit PT. Putera Pannjalu UPT Cempaka terdiri dari kegiatan pengisian polybag, penyapihan, penyiraman, perawatan dan perumputan. Waktu pengukuran prestasi kerja pada pukul 07:30 sampai 16:30 selama tujuh hari. Hasil pengukuran pengisian polybag dilakukan oleh tiga orang pekerja dengan rata-rata yang diperoleh selama satu minggu yaitu sebesar 202 polybag/jam/orang, untuk kegiatan penyapihan dilakukan oleh tiga orang pekerja dengan rata-rata 639 polybag/jam/orang. Sedangkan pada pengukuran prestasi kerja penyiraman yang dilakukan oleh dua orang pekerja memperoleh rata-rata prestasi kerja sebesar 79.838 polybag/jam/orang. Pada kegiatan perawatan diperoleh rata-rata sebesar 19.739 polybag/jam/orang dan untuk rata-rat prestasi kerja perumputan sebesar 14.898 polybag/jam/orang. Hasil pengukuran prestasi kerja di Kebun Bibit Putera Pannjalu UPT Cempaka dipengaruhi oleh umur, jenis kelamin dan lama kerja.